The Influence of Family on Student Interests in Determining Careers in Accounting Professions - La Ode Hasiara; Laras Kinanthi; Fatahul Rahman; Sri Hamdayani (SOSHUM : Jurnal Sosial dan Humaniora, 2023)
This study was conducted to determine the impact of the influence of parents on the interest of accounting students in determining a career as an accountant profession. Family members who have careers in accounting can influence the interest of accounting students in determining a career in the same field as their families. This research was conducted at the Samarinda State Polytechnic. Correspondents took as many as 50 correspondents. This study shows that family culture can influence accounting students to work as accountants. In Indonesia, the culture or habit of a strong bond with family and children is relatively high in choosing a career as an accountant profession. The result of this study proves that family has a significant influence on the selection of students for the accounting profession.